The private journal of Captain G. F. Lyon, of H. M. S. Hecla, during the recent voyage of discovery under Captain Parry - Lyon, G. F. (George Francis), 1795-1832. (London : J. Murray, 1824)
"Principally devoted to the narration of the peculiarities of the aborigines of the Arctic regions." -- Sabin, Dict. of books relating to America, Mode of access: Internet. Cogs.